Oil-Type Sunflower Cost-Return Budget in North Central and Northeast Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2002)
This publication provides estimated cost and returns for forward farm planning for producing sunflowers in north central and northeastern Kansas.
MF2144_2002_10
Keywords: MF2144; Crops; Economics; MF